Bryophytes Flora in Forest Patch of President Roxas, Cotabato, Philippines - Rikka Bianca Condes; Angel Lhi Dela Cruz; Marry Joy Badilles; Harold Fuentes; Romeo, Jr. Bordios; Amera Malaco; Sarip Tarita Ampatuan-Ali; Norolhaq Usop; Ryan Oños; Cherie Mangaoang (PT FORMOSA CENDEKIA GLOBAL, 2023)
This study was conducted to document bryophyte species in a forest patch of Pres Roxas, Cotabato, Philippines. A modified belt transect method was employed and 3 transect lines were established along the human-established trail. Moreover 5 1x1m2 quadrats were randomly established in each transect line. A total of 18 species of mosses and liverworts were identified. These species were classified under 11 families, and 14 genera. Nine (9) species of bryophytes were identified from both transect 1 and 2 while in transect 3, only 5 species thrived. Of the 18 species identified, Thiudium benguetense is found in the 3 transect lines established. Two (2) were identified endemic to the Philippines - Ecthropothecium ferrugineum and Thiudium benguetense. Moreover, similarity index showed that 86% are discordant species and each transect line harbors unique species of bryophytes. It is recommended that intervention in the protection and conservation of the remaining flora community of the mountain ecosystem must be employed given that community is dependent on the water coming from it.